Efficacy of infliximab as a switched biologic in rheumatoid arthritis patients in daily clinical practice. Issue 4 (2nd October 2018) - Umeda, Masataka; Koga, Tomohiro; Ichinose, Kunihiro; Takatani, Ayuko; Igawa, Takashi; Shimizu, Toshimasa; Fukui, Shoichi; Nishino, Ayako; Horai, Yoshiro; Hirai, Yasuko; Kawashiri, Shin-Ya; Iwamoto, Naoki; et al.
Abstract: To assess the efficacy and safety of switching to infliximab (IFX) from other biological disease-modifying anti-rheumatic drugs (bDMARDs) among Japanese patients with rheumatoid arthritis (RA) in daily practice. We examined 24 consecutive RA patients who had not achieved low disease activity (LDA) as the disease activity score-28 for rheumatoid arthritis with erythrocyte sedimentation rate (DAS28-ESR) despite previous bDMARD therapy in this cohort study. We attempted to determine predictive variables that are associated with achieving DAS28-ESR LDA at 22 weeks post-IFX introduction, by performing univariate analysis. The median DAS28-ESR at baseline was 5.41. Sixteen patients (66.7%) had been treated with a tumor necrosis factor inhibitor (TNF-i), and the other eight patients (33.3%) received a non-TNF-i (abatacept or tocilizumab). Nine patients (37.5%) achieved LDA or remission at 22 weeks. Univariate analyses showed that the variable to predict LDA achievement at 22 weeks was tender joints (>8 counts) at baseline (adjusted odds ratio, 0.10; 95% confidence interval, 0.01–0.63; p = .02). Nine adverse events were observed during the study period, and infection requiring hospitalization was observed in one patient. Switching to IFX is effective to achieve LDA or remission for RA patients refractory to bDMARDs.